SGLT2 inhibitors for improving hepatic fibrosis and steatosis in non-alcoholic fatty liver disease complicated with type 2 diabetes mellitus: a systematic review - Dwinata, Michael (Clin Exp Hepatol, 2020)
AIM OF THE STUDY: To evaluate the efficacy of sodium/glucose cotransporter-2 inhibitors (SGLT2i) in improving hepatic fibrosis and steatosis of non-alcoholic fatty liver disease (NAFLD) patients with type 2 diabetes mellitus (T2DM). MATERIAL AND METHODS: We searched CENTRAL, MEDLINE, and EMBASE and included any clinical trials involving patients with NAFLD and T2DM aged ≥ 18 years comparing efficacy of SGLT2i and other antidiabetic drugs in improving fibrosis and steatosis, irrespective of publication status, year of publication, and language. RESULTS: Five clinical trials were included. One study reported significant improvements in the controlled attenuation parameter 314.6 ±61.0 dB/m to 290.3 ±72.7 dB/m (p = 0.04) in the SGLT2i group measured by transient elastography. In patients with significant fibrosis, dapagliflozin treatment significantly decreased the liver stiffness measurement from 14.7 ±5.7 kPa at baseline to 11.0 ±7.3 kPa after 24 weeks (p = 0.02). One study reported a significant decrease in liver fat content 16.2% to 11.3% (p < 0.001) in the SGLT2i group compared to the control (p < 0.001). Three studies reported significant improvement in the liver-to-spleen ratio in the SGLT2i group after treatment 0.96 (0.86-1.07) to 1.07 (0.98-1.14), p < 0.01, 0.80 ±0.24 to 1.00 ±0.18, p < 0.001, and 0.91 (0.64-1.04) to 1.03 (0.80-1.20), p < 0.001 respectively. All studies reported a significant decrease in alanine aminotransferase with SGLT2i. CONCLUSIONS: SGLT2i is associated with positive effects on hepatic steatosis measured by non-invasive modalities. Further studies are needed to confirm the impact of SGLT2i on hepatic fibrosis and steatosis.